Fundamental Basis for Implementing Oxidant‐Free Au(I)/Au(III) Catalysis - Font, Pau; Ribas, Xavi (European journal of inorganic chemistry, 2021)
Oxidant‐free Au(I)/Au(III) catalysis can still be regarded as a young and promising chemistry. Because the first examples of gold catalysis were limited to the activation and functionalization of π‐C−C bonds and very little was known on fundamental organometallic transformations at gold, countless works during the past 15 years have been devoted to disclosing the elementary reactivity of gold and implementing it in catalysis. Remarkably, great emphasis on triggering oxidative addition at Au(I) has been placed, as the high redox potential of the Au(I)/Au(III) pair disfavors this reaction. In fact, different strategies such as strain release, ligand design and photochemistry have been proven successful at allowing the bottleneck oxidative addition to occur. These approaches have led to the rational development of oxidant‐free Au(I)/Au(III) redox catalysis, particularly catalytic cycles in cross‐coupling transformations where oxidative addition is usually the entry point to the cycle. Herein, the background story, the development process, and relevant examples of oxidant‐free gold‐catalyzed cross‐coupling reactions are reviewed. Gold catalysis is entering a new dimension through the development of oxidant‐free Au(I)/Au(III) catalytic protocols for cross‐coupling reactions. Here we discuss the different strategies used to overcome the reluctance of Au(I) to undergo oxidative addition without external oxidants, from the dedicated design of hemilabile ligands to achieve the stabilization of Au(III) species to the use of diazonium salts coupled with light irradiation.